Effectiveness and suitability from different testing technologies on integration and system testing in android applications (2019)
"Mobile applications have become a large part of what our society is right now. Many of the tasks that we have to do in our daily lives are supported by our mobile phones with some program that helps us to achieve such tasks. Many times we find ourselves trusting essential data, events, money, and other important things to this kind of applications and do not even hesitate in doing so. Testing is the primary tool that companies and developers have to ensure that the client gets reliable software in which the users can trust. It becomes crucial that the applications should be, not only tested but tested with the best technology for the particular case that it is trying to be checked. The primary purpose of this study is to generate a single centralized hub of information for people to go when they are trying to solve the question: Which testing technology should I use given the necessities of the Android project I am working on?"--Tomado del Formato de Documento de Grado.